Dashboard Application For Monitoring Patient Data In Hospitals - I Gusti Agung Ayu Sekarini; Anak Agung Sandatya Widhiyanti; Ni Made Rai Masita Dewi (Eduvest - Journal of Universal Studies, 2025)
In the increasingly advanced digital era, the healthcare sector faces significant challenges in effectively managing patient visit data. Monitoring patient visits, both inpatient and outpatient, is a crucial aspect of hospital management. This study aims to develop a dashboard application that can monitor inpatient and outpatient visit data in real-time and in an integrated manner at hospitals in Gianyar City. The problems faced include data inaccuracies, delays in decision-making, and lack of data integration from various sources. The research methods used include needs analysis through interviews and surveys, system design with architecture and prototype design, application development using the waterfall method, as well as testing using blackbox testing and application performance evaluation using usability testing. This application is designed to collect data from various sources, integrate it, and present it in an easily understandable visual form. The results of the study show that this dashboard application can improve the efficiency and accuracy of managing patient visit data, as well as support faster and more accurate decision-making. The conclusion of this study is that the developed dashboard application can help hospitals manage patient visit data more effectively, thereby improving the quality of healthcare services.